Found footage film in times of YouTube - Rosa, Carlos Adriano Jeronimo de (2016)
This article describes aspects of a research conducted in the field of found footage film and reappropriation cinema of archives. Structured entirely with materials extracted from YouTube, the film Untitled # 3: And what are poets for in a time of poverty? (2016) is a starting object that allows to address some issues about YouTube in relation to archivology. We adopted as a reference point the case study as a research method, considering the exploratory research and the analysis of content. For working the world as an archive, the found footage is presented under the form of an operating procedure which is appropriated for understanding the phenomena of image in the fields of archival science, of audiovisual media, of communication technologies, of information science. Basically referred to a form or a genre of film production which recycles, reissues and reframes images from other sources, in this study the found footage is configured as a critical method.